2021
DOI: 10.3390/nu13020407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Malnutrition Status on Muscle Parameter Changes over a 5-Year Follow-Up of Community-Dwelling Older Adults from the SarcoPhAge Cohort

Abstract: This study aimed to assess the impact of malnutrition on the 5-year evolution of physical performance, muscle mass and muscle strength in participants from the SarcoPhAge cohort, consisting of community-dwelling older adults. The malnutrition status was assessed at baseline (T0) according to the “Global Leadership Initiatives on Malnutrition” (GLIM) criteria, and the muscle parameters were evaluated both at T0 and after five years of follow-up (T5). Lean mass, muscle strength and physical performance were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…After the GLIM format was described, some authors have utilized relatively low degrees of inflammation, and independently from any diagnosis of chronic disease, for the fulfillment of the GLIM inflammation criterion. For example, in a recent cohort study of 534 community-dwelling older participants, malnutrition was diagnosed according to the GLIM criteria using an interleukin-6 cutoff value within the normal range of healthy persons (interleukin-6 > 3.84 pg/mL in men and >2.99 pg/mL in women) [23]. In another prospective cohort study of community-dwelling Chinese subjects (median age: 72 years), high-sensitivity CRP cut-off levels of ≥0.32 mg/dl in men and ≥0.38 mg/dl in women were used for the diagnosis of malnutrition according to GLIM [24].…”
Section: Discussionmentioning
confidence: 99%
“…After the GLIM format was described, some authors have utilized relatively low degrees of inflammation, and independently from any diagnosis of chronic disease, for the fulfillment of the GLIM inflammation criterion. For example, in a recent cohort study of 534 community-dwelling older participants, malnutrition was diagnosed according to the GLIM criteria using an interleukin-6 cutoff value within the normal range of healthy persons (interleukin-6 > 3.84 pg/mL in men and >2.99 pg/mL in women) [23]. In another prospective cohort study of community-dwelling Chinese subjects (median age: 72 years), high-sensitivity CRP cut-off levels of ≥0.32 mg/dl in men and ≥0.38 mg/dl in women were used for the diagnosis of malnutrition according to GLIM [24].…”
Section: Discussionmentioning
confidence: 99%
“…Disease-related malnutrition therefore leads to rapid skeletal muscle wasting, whereas age-related malnutrition is associated with a slower but progressive loss of muscle mass. The effects of protein catabolism are prominently reflected by lower muscle mass, muscle strength and function with severe implications for physical performance [ 17 ]. At the same time, malnutrition [ 18 ] but also reduced dietary protein intake per se [ 19 ] are associated with a decrease in bone mineral mass in higher age.…”
Section: Impact Of Malnutrition In the Oldmentioning
confidence: 99%
“…One particularity of malnutrition in older adults is that the impact appears to be more severe than in younger adults. Studies have not only shown that changes in body composition in malnutrition occur to a greater extent in older compared to younger adults [ 28 ], but also that recovery of low body cell mass or muscle mass is impaired in higher age following weight loss [ 17 ]. This predisposes malnourished older adults to the risk of developing the so-called geriatric syndromes which have been described as multifactorial syndromes typical in higher age [ 29 ].…”
Section: Impact Of Malnutrition In the Oldmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, physical performance, muscle mass, and muscle strength were significantly lower in malnourished than in well-nourished subjects. Unexpectedly, after 5 years, these parameters did not necessarily change, as described in the SarcoPhAge study [2].…”
mentioning
confidence: 65%